Determining factors affecting the influence of financial stakeholders- an empirical study on the islamic banking in Bangladesh - Khan, Nushrat Islam (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2018.